A metateatralidade intercultural: história, teatro e interculturalidade no teatro angolano contemporâneo: O cego e o paralítico, A órfã do rei e As formigas (2013-2014) - Christian Fernando dos Santos Moura (2016)
As events and facts Angolas historical past appear portrayed in three pieces of contemporary Angolan theater? What this picture offer in terms of cultural identity? As these parts operate production and transmission incorporating practices of the Angolan historical past and other contexts? How the characters, conflicts and historical themes are handled by this theater? In short what are the theoretical and identity contributions offered by the relationships made between the Angolan theater, history and cultural exchanges? Through these questions, this study aims to analyze, compare and understand the functioning of the historical theme of drama in three performances of different Angolan groups today, namely: O Cego e o Paralítico (2013), of the Elinga-Teatro, A Órfã do Rei (2013), of the Grupo Teatral Henrique Artes and As Formigas (2014), artist residency project Fundação Sindika Dokolo, with the ultimate aim to investigate tense runs and aesthetic-discursive expressions of intercultural metateatralidade analytical-functional theoretical operator for us conceptualized and adopted, which relates to procedures and dramaturgical resources, mainly the metalinguistic strategically used by these groups in the process of building their respective dramaturgy, which enable the establishment of intercultural dialogue between multiple sources and historical versions in their artistic and literary appropriation of the past in other cultures, in order to facilitate the reader's access / viewer to Angolan voices and knowledge of the cultural history of his people by means of cultural difference.